2004
DOI: 10.1108/03074350410768813
|View full text |Cite
|
Sign up to set email alerts
|

IPO‐related organizational change and long‐term performance: considerations of Dutch corporate officers

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Prior research has touched upon this issue tangentially and generated inconclusive and partial results. This paper echoes prior research indicating that IPOs prompt newly listed firms to reconfigure their MA practices (Kraus and Strömsten, 2012;O'Connor, et al 2004;O'Connor et al, 2006;Von Eije et al, 2004). It also provides detailed field-based evidence on how MA is implemented in these firms, even though some of this evidence appears dissimilar to that documented in prior research.…”
Section: Introductionmentioning
confidence: 38%
See 3 more Smart Citations
“…Prior research has touched upon this issue tangentially and generated inconclusive and partial results. This paper echoes prior research indicating that IPOs prompt newly listed firms to reconfigure their MA practices (Kraus and Strömsten, 2012;O'Connor, et al 2004;O'Connor et al, 2006;Von Eije et al, 2004). It also provides detailed field-based evidence on how MA is implemented in these firms, even though some of this evidence appears dissimilar to that documented in prior research.…”
Section: Introductionmentioning
confidence: 38%
“…However, studies addressing whether, how, and why IPOs shape the MA practices of newly listed firms are relatively limited, and the findings generated so far are inconclusive and partial. Some research has suggested that IPOs may prompt newly listed firms to change their MA practices (Kraus and Strömsten, 2012;O'Connor et al, 2004;O'Connor et al, 2006;Von Eije et al, 2004). However, Davila (2005) finds that IPOs did not lead small, young, and growing firms in Silicon Valley to change their control systems into more formal ones.…”
Section: Ipos and Management Accounting Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Firms can use the IPO proceeds and capital market access for strategic acquisitions and to compete more aggressively (Maksimovic and Pichler 2001;Schultz and Zaman 2001;Chod and Lyandres 2011;De Jong et al 2012). Also, a firm's organizational structure may benefit from the preparations of the IPO, and from the disciplinary role of reporting requirements, governance standards and visibility after the IPO (Burton et al 2004;von Eije et al 2004). Pagano et al (1996Pagano et al ( , 1998 show that Italian firms borrow more cheaply after an IPO.…”
Section: Changes In Business Relationships: Credibility and Reputationmentioning
confidence: 99%